Generation and differentiation of an induced pluripotent stem cell line (FMCPGHi006-A) from a patient with Duchenne muscular dystrophy carrying exons 42–43 deletion in the DMD gene - Yue Chang; Xiuyi Ai; Ruo Wu; Shu Zhang; Pei Zhang; Shiwen Wu (Stem Cell Research, 2025)
Duchenne muscular dystrophy (DMD) is an X-linked recessive genetic disorder characterized by severe progressive muscle atrophy. Although treatments for respiratory complications have improved, dilated cardiomyopathy (DCM) with heart failure remains the leading cause of death in patients with DMD. We generated an induced pluripotent stem cell (iPSC) line from a patient with a deletion of exons 42–43 in the DMD gene and differentiated it into cardiomyocytes (iPSC-CMs). This iPSC line exhibited normal morphology, karyotype, pluripotency marker expression, and trilineage differentiation, while the iPSC-CMs displayed a typical cardiomyocyte morphology and expressed specific markers.